The uplift load capacity of an enlarged base pier embedded in dry sand - Nazir, Ramli (Springer Verlag, 2015)
The purpose of this research is to determine the capability of (and the factors which affect the performance of) an enlarged base pier in resisting uplift capacity. Experiments were conducted in the reinforced bin box of an enlarged base pier with a shaft diameter ranging from 30 to 50 mm, base diameters between 75 and 150 mm and base angles of a = 30°, a = 45° and a = 60°. Tests were conducted in both loose and dense sand packing. A failure mechanism was studied in a glass box for loose and dense sand packing. A dry sand with a unit weight of ?d = 14.80 kN/m3 and ?d = 17. 0 kN/m3 was achieved for loose and dense packing, respectively. Increasing the bell angle and shaft diameter would result in a decrease of the net uplift capacity and failure displacement. This is due to the reduction in the amount of the sand column above the bell that resists the uplift of the pile. Failure displacements at a constant base diameter generally increased considerably with the increase of the embedment ratio but decreased with the increment of the sand density. It is thus apparent that the shaft diameter, bell diameter and bell angle are geometric factors which, together with the embedment ratio and the sand density, should be taken into account in the design of enlarged base piers.